Information and Crime Perceptions: Evidence from a Natural Experiment - Nicola Mastrorocco; Luigi Minale (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
This paper investigates the influence of media on the beliefs and perceptions individuals hold, with a focus on crime perceptions. We study the case of Italy, where the majority of television channels have been under the influence of the former Prime Minister Silvio Berlusconi for more than a decade. First, we document that these channels systematically over represent crime news compared to others. We then test if individuals revise their perceptions about crime when exposure to news programs broadcast by a specific group of partisan channels is reduced. In order to identify the causal effect we exploit a natural experiment in the Italian television market where the staggered introduction of the digital TV signal led to a drastic drop in the viewing shares of the channels above. Combining unique data on each channel's crime news coverage and prime-time viewing shares, we find that reduced exposure to crime related news decreased concerns about crime, an effect that is mainly driven by older individuals who, on average, watch more television and use alternative sources of information (such as Internet, radio and newspapers) less frequently. Finally, we show that this change in crime perceptions is likely to have important implications for voting behaviour.
Keywords: D72; D83; K42; L82; 330; information; mass media; persuasion; crime perceptions